Study on the Wetland Changes Monitoring of Wuliangsuhai Lake Based on Average Deviation / 基于偏差平均值的乌梁素海湿地变化监测研究 - 韦玮; 崔丽娟; 李胜男; 郭嘉 (Forest research (Beijing), 2012)
Based on the TM/ETM + remote sensing data of Wuliangsuhai wetland in 2003-2011, the methods of ratio vegetation index and bond combination was used to obtain the information about the areas of open water, water plants, reed and farmland in Wuliangsuhai wetland and the change of area and their patterns were analyzed. By using the method of data point’s average absolute deviations, the change rates of above-mentioned areas were calculated and the changing trend was estimated. Based on these comparison and analysis, the dynamics change of Wuliangsuhai wetland was predicated and the results are as follows: the change rate of open water is 26.56%, and that of water plants and reed are -20.66% and -1.49% respectively, i.e. the area of open water will increase by 33.57 km2,while the areas of water plants and reed will decrease by 21.02 km2 and 4.92 km2 respectively in 2012. 采用乌梁素海地区2003-2011年的TM/ETM+遥感数据,利用比值指数和波段组合的方法提取了乌梁素海水域、水草、芦苇和农田等信息,并分析了9年间乌梁素海地区各类型面积的增减情况及其变化规律,采用数据点绝对偏差的平均值方法,概算出各类型面积的变化率,根据变化率的值估算出各类型面积变化的